New Frontiers in Gut Nutrient Sensor Research: Nutrient Sensors in the Gastrointestinal Tract: Modulation of Sweet Taste Sensitivity by Leptin - Nao Horio; Masafumi Jyotaki; Ryusuke Yoshida; Keisuke Sanematsu; Noriatsu Shigemura; Yuzo Ninomiya (Elsevier, 2010)
The ability to perceive sweet compounds is important for animals to detect an external carbohydrate source of calories and has a critical role in the nutritional status of animals. In mice, a subset of sweet-sensitive taste cells possesses leptin receptors. Increase of plasma leptin with increasing internal energy storage in the adipose tissue suppresses sweet taste responses via this receptor. The data from recent studies indicate that leptin may also act as a modulator of sweet taste sensation in humans with a diurnal variation in sweet sensitivity. The plasma leptin level and sweet taste sensitivity are proposed to link with post-ingestive plasma glucose level. This leptin modulation of sweet taste sensitivity may influence an individual's preference, ingestive behavior, and absorption of nutrients, thereby playing important roles in regulation of energy homeostasis. Keywords:: sweet taste, leptin, modulation, energy homeostasis, gastrointestinal tract